Pengaruh Penggunaan Limbah Sabut Kelapa Sebagai Filler Terhadap Kinerja Karakteristik Marshall pada Campuran Aspal Porus - sri Gusty (Universitas Sulawesi Barat, 2022)
Porous asphalt is a hot asphalt mixture between open-graded aggregate and modified asphalt with a certain ratio. However, there is a weakness in porous asphalt, which is that it has lower marshall stability. To improve the stability of road pavement performance, it is necessary to add additional material to the mixing of porous asphalt. So far, the filler materials that are often used in asphalt mixtures are cement, lime, stone ash, and fly ash. However, the supply of these fillers is limited and also relatively expensive. In this study, coconut coir was added material because coir ash is one of the natural products that can be continuously renewed and sustainable. Coconut has been planted almost all over Indonesia and coconut is one of the good natural resources. So far, the people of Makassar use coconuts to make copra, coconut oil, and drinks, as an ingredient for making ropes, washing dishes, and as fuel for cooking. Coir ash from the burning of coconut husks cannot be used anymore and is usually thrown away by the community and coconut coir has not been used optimally. The purpose of this study was to determine the value of the marshall characteristics in the asphalt mixture using coconut coir ash as a filler with a 60/70 asphalt pen. Variations of coconut coir filler 0%, 40%, 50% with asphalt content of 6%. Initial testing is done by making coconut coir ash as a filler material that will be used in making test objects. Based on the results of the Marshall characteristics test that the test object using coconut coir ash, some of Marshall's characteristics have met the REAM specification of 0% variation, 50% there is an optimum value, namely 40% variation but the VFB value does not meet the REAM specification.